Microwave-assisted organocatalysis: phosphine-mediated Tomita Zipper cyclization affording functionalized spirooxindole. Issue 33 (17th August 2016) - Zhang, Xiao-Yan; Shen, Ze; Hu, Li-Li; Wang, Liang-Jun; Lin, You-Shuai; Xie, Jian-Wu; Cui, Hai-Lei
Graphical abstract: Highlights: A phosphine-mediated Tomita Zipper cyclization has been developed. The in situ generated α-nucleophile as key intermediate is proposed. Moderate to good yields and diastereoselectivities can be achieved. Abstract: A microwave-assisted and phosphine-mediated Tomita Zipper cyclization of dicyanomethylideneoxindoles and ynones has been developed. Various functionalized spirooxindoles with five-membered carbocyclic ring can be obtained in moderate to good yields with moderate to excellent diastereoselectivities through in situ generation of α-nucleophile (up to 87% yield, >20:1 dr).